Peningkatan Kemampuan Analisis Struktur Teks Berita Siswa Kelas XI TFLM 2 SMKN 5 Surabaya dengan Strategi SQ3R - Faudia Miranti; Kaswadi Kaswadi; Moch. Hadiyono (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose is to develop the students of class XI-TFLM 2 of SMK Negeri 5 Surabaya in understanding the structure of news text by using SQ3R technique. The main problem identified is that students are unable to recognize the important elements of news text, such as title, introduction, news content, and conclusion. This research method includes two action cycles using the SQ3R strategy and consists of the following steps: research, questioning, reading, reciting, and reviewing. In Cycle I, this strategy was introduced to improve students' understanding of news text structure, resulting in an increase in students' average score from 55.82 points in the pre-action to 71.06 points. Based on the reflection of Cycle I, it was found that students still had difficulty distinguishing and analyzing the elements of news structure. In the second cycle, they strengthened the SQ3R strategy through group discussions and extensive reading, so that their average score increased to 80.76. These results show that the SQ3R strategy is effective in improving students' news text analysis skills. The improvement of students' ability in analyzing the structure of news texts is reflected in the better results in cycle II, showing the potential of this method as an effective approach in Indonesian language learning. This study recommends a more comprehensive application of the SQ3R strategy to improve news text analysis skills in secondary education.